METAL HEATING DEVICE - Kholov Orif Tolibovich; Hamdamova Lola Olimjon daughter; Gayratova Gulzoda San'at daughter (Research Parks Publishing LLC, 2020)
Metallurgy (Greek: metallurgeo) is the study of the extraction of metals from ores or metal-containing substances and the